The Changing Financial Landscape : Opportunities and Challenges for the Middle East and North Africa - Grais, Wafik; Kantur, Zeynep (World Bank, Washington, DC, 2014)
Economists have come to acknowledge that finance matters for development more, and in more ways than had been recognized for a long time. Changes in the financial services industry are providing immense possibilities for economic development. Grais and Kantur present a framework to help understand the changes occurring in the financial landscape. They also attempt to lay out the opportunities and the challenges the Middle East and Northern Africa region faces in light of these changes. The framework views financial development as a two-way, continuous, and dynamic interaction between, on the one hand, three driving forces shaping the industry and, on the other hand, four stylized dimensions of financial services. These driving forces jointly modify the financial landscape and are at the same time influenced by the effects of these changes. The three driving forces are financial liberalization, technological changes, and market innovation in response to demands for financial services. The four dimensions of financial services that are altered by the forces at play are disintermediation, institutionalization, modernization, and globalization. The authors provide a strategic perspective on the opportunities and challenges the profound changes in the financial industry bring to the Middle East and North Africa region, its policymakers, and market participants.